IDENTIFICATION OF THE GENES LR17 AND LR26 FOR RESISTANCE TO LEAFRUST (PUCCINIA TRITICINA) IN SOME EUROPEAN WHEAT CULTIVARS - Abdul, S. D. (Emirates Journal of Food and Agriculture, 2011)
In the present investigation, the identification of genes LR17 and LR26 for resistance to leaf rust was carried out in some European wheat cultivars. The allelic relationship between the near-isogenic line [RL6008] having Lr17 and the wheat cultivars Hobbit, Fundin and Tara crossed in a diallel without reciprocals and with the susceptible control variety Armada were tested. Progenies of these crosses were tested for reaction to Puccinia triticina isolate WBRP 85- 31 that has avirulence for Lr17 at high temperature. Crosses between RL6008, Hobbit, Fundin and Tara with the susceptible check Armada segregated in 1:2:1 ratio in F3 progenies. It suggests the presence of a single gene for resistance to leaf rust. In addition, the F3 populations of the crosses between Hobbit, Fundin and Tara with line RL6008 were all resistant, thus confirming allelic relationship between Lr17 and the resistance gene in these cultivars. Also crosses were made between cultivar Tara and the susceptible control Armada which segregated 3:1 ratio in F2 population when tested with isolate WBRP 82-1. This suggests the presence of a single gene for resistance in Tara. When Clement and Tara were crossed all the plants in the F2 population were resistant, thus suggesting allelic relationship in the resistance gene present in these cultivars. Both Clement and Tara were shown to have the seed protein ?secalin’ associated with the chromosome 1R of rye that is known to have the Lr26 gene. It is therefore suggested that the leaf rust resistance gene identified in Tara and Clement is likely to be Lr26.